Description of Students Learning Independence in Online Science Learning at Private MTs Nur Ikhsan Ndori - M B. U. Kaleka; A. B. Baluk; H. Doa (Journal of Science Education Research, 2023)
This study aims to describe students learning independence in online science learning in class XI MTs Swasta Nur Ikhsan Ndori. This type of research uses descriptive research. The subjects in this study were grade IX students of MTs Nur Ikhsan Ndori. While the object in this study is a description of student learning independence in online science learning. The data collection technique in this research is a questionnaire. The results obtained from this research show that students' learning independence in online science learning is categorized as good, with the acquisition of the percentage of each indicator, namely for the confidence indicator, the percentage is 66% in the good category, the active indicator in learning is 54% in the sufficient category, and the indicator for discipline in learning is sufficient. learning has a percentage of 54% in the sufficient category, the responsibility indicator with a percentage of 57% in the good category, and the initiative indicator with a percentage of 59% in the good category. The average percentage gain of the five indicators is 58%. This shows that the learning independence of students at MTs Nur Ikhsan Ndori is categorized as good.